Toxicities of active constituent isolated from Thymus vulgaris flowers and its structural derivatives against Tribolium castaneum (Herbst) - Lee, Hee-Kwon; Lee, Hoi-Seon (Applied biological chemistry, 2016)
Insecticidal activity of 2-isopropyl-5-methylphenol isolated from Thymus vulgaris oil and its derivatives against Tribolium castaneum adults and larvae were evaluated using contact and fumigant bioassays. To elucidate the structure–activity relationship, 2-isopropyl-5-methylphenol and its derivatives were determined. Based on the LD 50 values, 2-isopropylphenol was most toxic to T. castaneum adults and larvae, followed by 4-isopropylphenol, 2-methylphenol, 3-methylphenol, and phenol in contact and fumigant bioassays. These results indicate that the introduction of a functional group such as methyl and isopropyl group into the phenol skeleton has an important influence on contact and fumigant toxicities. Furthermore, 2-isopropyl-5-methylphenol and its derivatives could be used as an alternative to control stored-grain insects.